THE RELATIONSHIP BETWEEN HUMAN RESOURCES AND PLANNING WITH MINIMUM COVERAGE OF HEALTH CARE SERVICES IN KONAWE REGENCY: HUMAN RESOURCES AND PLANNING - Daslan Daslan; La Ode Saafi; Tasnim Tasnim (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2022)
Background: The preliminary study  revealed that there were main problems in the implementation of the 2020 Health Development Program related to Minimum health service standard. These problems such as the availability of human resources that greatly contribute to service management at the public health centre in the form of planning, mobilizing and implementing in achieving goals, in this case related to the quality and equitable distribution of health workers as the spearhead of program implementation which is the supervision and assessment of the public health centre so that it will influential in the process of service implementation management according to minimum service standars. This study aims to analyseThe relationship between human resourcesand planning with minimum coverage of health care services in Konawe Regency. Methods: This study uses a quantitative research design with a approachcross sectional study.The population is the entire person in charge of the minimum service standars of each public health centre in the working area of Konawe Regency, namely 42 respondents. The number of samples using the Slovin formula is 38 respondents with a sampling technique using simple random sampling. Result: There is a strong relationship between human resources, planning to the coverage of minimum service standards. Conclusion: Monitoring the minimum service standards and providing feedback on the results, conducting training and increasing the availability of health service facilities and infrastructure.